Electrophysiological properties and calcium handling of embryonic stem cell-derived cardiomyocytes - Jae Boum Youm (Integrative Medicine Research)
Embryonic stem cell-derived cardiomyocytes (ESC-CMs) hold great interest in many fields of research including clinical applications such as stem cell and gene therapy for cardiac repair or regeneration. ESC-CMs are also used as a platform tool for pharmacological tests or for investigations of cardiac remodeling. ESC-CMs have many different aspects of morphology, electrophysiology, calcium handling, and bioenergetics compared with adult cardiomyocytes. They are immature in morphology, similar to sinus nodal-like in the electrophysiology, higher contribution of trans-sarcolemmal Ca2+ influx to Ca2+ handling, and higher dependence on anaerobic glycolysis. Here, I review a detailed electrophysiology and Ca2+ handling features of ESC-CMs during differentiation into adult cardiomyocytes to gain insights into how all the developmental changes are related to each other to display cardinal features of developing cardiomyocytes.